2020
DOI: 10.18280/ts.370606
|View full text |Cite
|
Sign up to set email alerts
|

A Face Detection Method Based on Skin Color Model and Improved AdaBoost Algorithm

Abstract: This paper integrates skin color model and improved AdaBoost into a face detection method for high-resolution images with complex backgrounds. Firstly, the skin color areas were detected in a multi-color space. Each image was subject to adaptive brightness compensation, and converted into the YCbCr space, and a skin color model was established to solve face similarity. After eliminating the background interference by morphological method, the skin color areas were segmented to obtain the candidate face areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The research of face detection has important research value due to the variability of facial expression, skin color, and illumination. Yong and Yanru [1] studied the face detection based on skin color features and found that the difference in skin color is obvious under different illumination levels. In order to solve this problem, it uses YCbCr and HIS two skin color space lighting as the technical basis.…”
Section: Introductionmentioning
confidence: 99%
“…The research of face detection has important research value due to the variability of facial expression, skin color, and illumination. Yong and Yanru [1] studied the face detection based on skin color features and found that the difference in skin color is obvious under different illumination levels. In order to solve this problem, it uses YCbCr and HIS two skin color space lighting as the technical basis.…”
Section: Introductionmentioning
confidence: 99%
“…Face detection [10] is a critical phase in this framework. The initial stage of the face mask detection system is to detect faces in stored and real-time images.…”
Section: Face Detector Ssd Modelmentioning
confidence: 99%
“…In this paper, the AdaBoost [13] algorithm is chosen as the classifier. The algorithm first trains several weak classifiers with the sample set, and then combines these weak classifiers into a strong classifier.…”
Section: Figure 2 Calculation Process Of Lbp Featurementioning
confidence: 99%